Scientists at Stockholm University - Dahlgren, Alfred, 1861–1908 (1895)
Black and white photograph of scientists at Stockholms Högskola, now Stockholm University, 1895 posed sitting and standing around a table. Pictured standing from left to right are Laggreen, Rosebowski, possibly Otto Nikolaus Witt (1853-1915), Nils Strindberg (1872-1897), Ericson, Andersson, and seated from left to right are Luggen, Viktor Rothmund (1870-1927), Svante Arrhenius (1859 - 1927), Georg Bredig (1868-1944).
Keywords: Arrhenius, Svante, 1859-1927; Bredig, Georg, 1868-1944; Rothmund, Viktor, 1870-1927; Stockholms universitet; Chemists; Strindberg, Nils, 1872-1897